2010
DOI: 10.1177/1934578x1000500605
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Antiparasitic Abietane Diterpenoids from the Roots of Clerodendrum eriophyllum

Abstract: Chromatographic separation of the roots of a Kenyan medicinal plant, Clerodendrum eriophyllum, led to the isolation of ten abietane diterpenoids (1-10), one of which (1) was isolated for the first time from a natural source. Using spectroscopic data, the structure of 1 was determined to be 12-hydroxy-8,12-abietadiene-3,11,14-trione. Circular dichroism (CD) spectra showed that the stereochemistry of compounds 1, 3, and 6-8 belongs to the normal series of abietane diterpenes, which confirmed the absolute stereoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 24 publications
4
33
0
Order By: Relevance
“…These results are in agreement with literature data on diterpenoids isolated from other plant species [1925]. Our result for taxodione ( 3 ) was consistent with that obtained by Machumi et al [19] who reported antileishmanial and antimalarial activities for taxodione isolated from the roots of Clerodendrum eriophyllum .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…These results are in agreement with literature data on diterpenoids isolated from other plant species [1925]. Our result for taxodione ( 3 ) was consistent with that obtained by Machumi et al [19] who reported antileishmanial and antimalarial activities for taxodione isolated from the roots of Clerodendrum eriophyllum .…”
Section: Resultssupporting
confidence: 94%
“…Our result for taxodione ( 3 ) was consistent with that obtained by Machumi et al [19] who reported antileishmanial and antimalarial activities for taxodione isolated from the roots of Clerodendrum eriophyllum . Van Zyl et al [20] reported on seven abietane diterpenes from the Plectranthus species P. hadiensis , P. lucidus , P. ecklonii , P. purpuratus subsp.…”
Section: Resultssupporting
confidence: 92%
“…18 Compound 10 has been described in the past as a potent antileishmanial agent against L. donovani promastigotes in vitro after it was isolated from other plant species, including Clerodendrum eriophyllum Gürke (Verbenaceae) and Cupressus sempervirens L. (Cupressaceae). 43,44 More recently, this compound has been reported to be an inhibitor of human and trypanosomal farnesyl diphosphate synthase (FPPS), 45 which could explain the biological activity observed both in this study and in others, but putatively for 2 as well based on their structural similarity. Many of the compounds isolated from the active fraction were tested but were inactive (IC 50 >10 μM) in the antileishmanial bioassays.…”
Section: Resultsmentioning
confidence: 62%
“…Compound NP-15 (taxodione) is an abietane diterpenoid, which can be separated from the roots of a Kenyan medicinal plant, Clerodendrum eriophyllum. 16 NP-15 has a simple, different scaffold compared with NP-2, NP-3 and NP-9, and its p300 HAT inhibitory activity may be due to predicted hydrogen bonds with the three key residues observed in docking studies (Fig. 3D).…”
mentioning
confidence: 92%